Modelagem hidrogeológica aplicada à análise de transporte de contaminantes: estudo prospectivo da propagação de contaminação em aquífero livre poroso - Edilaine Gomes da Silva (2018)
The groundwater quality is susceptible to being affected by socioeconomic activities, namely by the different forms of land use and occupation. In addition, several studies have shown the groundwater influence on lakes, including the contaminants transport. The quantification of the phenomena that involve flow and transport in these systems can be obtained through mathematical modeling, since due to the complexity of the medium, a complete survey with field data, is not always feasible or possible to be performed. The present work consisted in the behavior of plumes of subterranean contamination study by flow and contaminants transport hydrogeological modeling in the free aquifer of the Vargem das Flores reservoir watershed MG. Firstly, the conceptual model that was the basis for obtaining the solid numerical model was elaborated. In its development, data were collected to monitor water levels and rainfall, as well as data available in the literature for the hydrodynamic parameters of the main aquifer lithologies. After the data treatment and the conceptual and numerical models assembly, the water levels were calibrated. The numerical method used was the finite element method used in the computational algorithm FEFLOW. With the flow numerical model calibrated, the benzene transport in the aquifer was simulated, resulting from hypothetical accidents involving tankers in the Rodoanel Norte and a sensitivity analysis of the transport parameters was carried out. The conceptual hydrogeological model represented in a simplified way the flow of the aquifer in the region, represented in a more complex way in the numerical modeling. The calibration of this model allowed us to obtain a coherent model, which indicated the predominant direction of the water from northeast to southwest, that is, towards the reservoir. Finally, the benzene transport results indicated that the Rodoanel contamination does not directly reach the Vargem das Flores reservoir, however, it can reach indirectly through the main superficial water courses tributaries to the reservoir contamination. The sensitivity analysis of this step results indicated that variations of the parameters did not generate significant changes in the contamination plume reach nor in the benzene concentrations. The dispersivity parameters and the decay coefficient were the most sensitive to the model.